2016
DOI: 10.1038/ncomms10477
|View full text |Cite
|
Sign up to set email alerts
|

p38γ and δ promote heart hypertrophy by targeting the mTOR-inhibitory protein DEPTOR for degradation

Abstract: Disrupted organ growth leads to disease development. Hypertrophy underlies postnatal heart growth and is triggered after stress, but the molecular mechanisms involved in these processes are largely unknown. Here we show that cardiac activation of p38γ and p38δ increases during postnatal development and by hypertrophy-inducing stimuli. p38γ/δ promote cardiac hypertrophy by phosphorylating the mTORC1 and mTORC2 inhibitor DEPTOR, which leads to its degradation and mTOR activation. Hearts from mice lacking one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 49 publications
8
68
0
Order By: Relevance
“…DEPTOR is an mTORC1 inhibitor [30, 31], which is closely related to cell proliferation, inflammation, obesity, and cancer [32, 33] and directly connected with cardiovascular disease [34, 35]. One study reported that DEPTOR regulates vascular EC activation and contributes to proinflammatory and angiogenic responses in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…DEPTOR is an mTORC1 inhibitor [30, 31], which is closely related to cell proliferation, inflammation, obesity, and cancer [32, 33] and directly connected with cardiovascular disease [34, 35]. One study reported that DEPTOR regulates vascular EC activation and contributes to proinflammatory and angiogenic responses in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…To test if p38 is required for the negative correlation of cell size with G1 length, we 87 examined a panel of specific inhibitors against MAPK pathways and tested whether any of these inhibitors break 88 the negative correlation induced by rapamycin. Significantly, inhibition of p38, but not the JNK or ERK 89 pathways, consistently breaks the negative correlation between size and proportion of cells in G1 (Figure 2 B-E, 90 isoforms with regard to size control (13,16). One difference between the chemical inhibition and the knockdown 96 experiments is a greater reduction in cell size observed following chemical inhibition of p38.…”
Section: Results 27mentioning
confidence: 81%
“…In this way, the β-TrCP increases mTOR activity resulting in an inhibition of autophagy (Figure 3A) 95,96 . Multiple studies have identified DEPTOR in cardiomyocytes, implicating p38 activity in its regulation 97 .…”
Section: Therapies Targeting Cardiac Autophagy To Promote Cardioprotementioning
confidence: 99%